The Effect of Giving Moringa Juice on Breast Milk Nutrition among Postpartum Mothers - Musrif, Fitriyanti; Rohmawati, Wahidah (Jurnal Bidan Cerdas, 2023)
Introduction: Based on data from the United Nations Children's Fund (UNICEF) in 2021, the percentage of babies aged 0-5 months who are exclusively breastfed in the world is 48%. Babies really need exclusive breast milk because it is rich in nutrients, including breast milk containing macro and micronutrients as well as vitamins and minerals. Objective: To determine the effect of giving Moringa juice on breast milk nutrition for postpartum mothers. Method: This type of research is quantitative with a pre-experimental method with a one-group pretest-posttest design. The research was conducted in the Lawa Community Health Center Work Area for 7 days in September 2023. The sample population was 30 people. The sample used in this study was 10 postpartum mothers who breastfed their babies. The sampling technique is purposive sampling. Data analysis used the Wilcoxon test. Results The results showed that before being given Moringa juice, the protein content of breast milk was 8.77 ppm, and after being given Moringa juice, the protein content of breast milk was 18.54 ppm with a p-value of 0.005.  Conclusion: Giving Moringa juice affects the nutritional levels of postpartum mothers.